2008
DOI: 10.1111/j.1398-9995.2008.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids inhibit degranulation of mast cells in allergic asthma via nongenomic mechanism

Abstract: The study suggested for the first time that nongenomic pathway was involved in GCs' rapid inhibition on allergic asthma, and raised the possibility of new therapeutic strategies for allergic diseases including asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…, we verified modulation of Ca 2? signaling might play an key role in the non-genomic action of GCs [12]. Regrettably, the study showed that cAMP was not involved in the rapid effect of the novel GCs (HG).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, we verified modulation of Ca 2? signaling might play an key role in the non-genomic action of GCs [12]. Regrettably, the study showed that cAMP was not involved in the rapid effect of the novel GCs (HG).…”
Section: Discussionmentioning
confidence: 99%
“…plus 1 ml of suspension (10 mg ovalbumin in saline, i.m.). Then, 30 days later, animals were challenged to allergic asthma reaction with an aerosol of antigen (ovalbumin suspended in saline, 10 mg/ml) for 25 s [12]. In addition, the pulmonary function parameters were monitored continuously.…”
Section: Allergic Reaction Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that glucocorticoids may have an indirect anti-inflammatory impact on MCs, with the postulated mechanism being a reduction of stem cell factor production by fibroblasts ( Da Silva et al ., 2002). Alternatively, they may also have direct impacts by reducing IgE binding to the FcεRI receptors, thereby down regulating the expression of these receptors on the cell membrane of the MCs and inhibiting MC degranulation in vitro ( Finotto et al ., 1997; Yamaguchi et al ., 2001; Zhou et al ., 2008). Prior to the current study, the only report of expression of GR in human MCs was from Oppong et al .…”
Section: Discussionmentioning
confidence: 99%